Nano-curcumin Attenuates Nephropathic Lesions Induced by Chronic Ketoprofen Administration in Rats: role of Cyclooxygenase-1 - Ali, Marwa Farouk; Sadek, Amira S.; Abd Elghfar, Sary K.; Taha, Mokhtar (Journal of Advanced Veterinary Research, 2022)
Â Ketoprofen can relieve pain and inflammation associated with many diseases but, it may cause unwanted side effects especially in kidneys. Curcumin nanoparticles (CurNPs) have a protective effect related to their anti-inflammatory and antioxidant properties. The present study examined the protective role of cyclooxygenase-1 (COX-1) in kidney induced by CurNPs against Ketoprofen-induced nephropathic injury. Twenty adults male Wistar rats were randomly assigned into four groups (n=5); Ketoprofen administered group, Ketoprofen and CurNPs- treated group, CurNPs treated group and control group. Animals were sacrificed 6 weeks post-administration. Blood serum samples were used for evaluation of urea, creatinine, lipid peroxidation (MDA) and total antioxidant capacity (TAC) levels. Kidney specimens were collected for histopathology and COX-1 expression was studied as well. The histopathological results of kidney in Ketoprofen administrated group showed focal segmental and global glomerulosclerosis, periglomerular fibrosis, intratubular casts and lytic necrosis of renal tubular epithelium. The pathological lesions were decreased to be mild changes in kidney of Ketoprofen and CurNPs- treated group. Immunhistochemical examination of COX-1 showed negative expression in Ketoprofen group which was attenuated in Ketoprofen and CurNPs- treated group. The biochemical examination revealed that animals in Ketoprofen administrated group showed significant increase in urea, creatinine, and MDA while TAC levels were numerically decreased. These results were attenuated in Ketoprofen and CurNPs- treated group. Co-administration of CurNPs with Ketoprofen caused reduction in kidney parameters and MDA with numerical improvement in TAC. In the present study,Â CurNPs have obvious protective effects on nephropathic lesions induced by Ketoprofen.